Canadian International Petroleum Conference 2002
DOI: 10.2118/2002-259
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of In Situ Horizontal Fractures in Shale Due to Steam Injection

Abstract: Thermal recovery processes such as cyclic steam stimulation and steam assisted gravity drainage involve steam injection of large volume into oil sand formation. Dilatation of oil sand formation due to steam injection induces stresses and deformations in the shale overburden. Natural horizontal fissures or fractures of large extent with no tensile and cohesive strength are commonly found in the shale formation. New fractures will be initiated at these in-situ horizontal fracture tips if the stresses and deforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In addition, in-situ stress state change due to geological movements (e.g. a thrust fault) (Maxwell et al 2007), secondary or enhanced oil recovery (Wright et al 1997;Wong and Chau 2004) may result in significant growth of horizontal fractures during fracturing. Daal and Economides (2006) studied hydraulically fractured wells in square and rectangular patterns, and they concluded that a dimensionless fracture conductivity of 1.6 will yield the highest productivity for production systems with proppant number below 0.1.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in-situ stress state change due to geological movements (e.g. a thrust fault) (Maxwell et al 2007), secondary or enhanced oil recovery (Wright et al 1997;Wong and Chau 2004) may result in significant growth of horizontal fractures during fracturing. Daal and Economides (2006) studied hydraulically fractured wells in square and rectangular patterns, and they concluded that a dimensionless fracture conductivity of 1.6 will yield the highest productivity for production systems with proppant number below 0.1.…”
Section: Introductionmentioning
confidence: 99%